PERKEMBANGAN KEMAMPUAN MOTORIK KASAR ANAK USIA DINI MELALUI PERMAINAN TRADISIONAL GOBAK SODOR DI PAUD CAHAYA GEMILANG DUSUN LIMBORO KECAMATAN HUAMUAL KABUPATEN SERAM BAGIAN BARAT - Junita L. Kundre; Ninda Ali; Lambertus J. Lokollo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research addresses the issue of underdeveloped gross motor skills among 5-6 year old children at PAUD Cahaya Gemilang in Limboro Village, Huamual District, West Seram Regency, where learning activities predominantly focused on fine motor skills while gross motor development was neglected through monotonous teaching methods and limited facilities. The study aimed to determine how traditional Gobak Sodor games could enhance gross motor skills development in early childhood. Using a Classroom Action Research (PTK) methodology conducted over two cycles with two meetings each, the research involved 10 children aged 5-6 years. Data collection employed observation sheets and documentation, with analysis calculated through percentage achievement. Results demonstrated significant improvement from Cycle I to Cycle II: in the first cycle, 4 children (40%) developed very well (BSB), 2 children (20%) developed as expected (BSH), and 4 children (40%) began developing (MB); by the second cycle, 8 children (80%) achieved very good development (BSB), 1 child (10%) developed as expected (BSH), and only 1 child (10%) was beginning to develop (MB), with no children remaining in the "not developed" category. The findings confirm that traditional Gobak Sodor games effectively enhance gross motor skills development through coordinated body movements, agility training, and rule-based physical activities.